Molecular characterization of methicillin-resistant and -susceptible Staphylococcus aureus recovered from hospital personnel. Issue 12 (12th December 2020) - Xu, Zhen; Li, Xiaodong; Tian, Dan; Sun, Zhuoyu; Guo, Liqiong; Dong, Cuixia; Tang, Naijun; Mkrtchyan, Hermine V.
Abstract : Introduction. Methicillin-resistant Staphylococcus aureus (MRSA) is one of the major causes of hospital-acquired infections. Over the past two decades MRSA has become 'epidemic' in many hospitals worldwide. However, little is known about the genetic background of S. aureus recovered from hospital personnel in China. Hypothesis/Gap Statement. The diversity of S. aureus genotypes warrants further surveillance and genomic studies to better understand the relatedness of these bacteria to those recovered from patients and the community. Aim. The aim of this study was to determine the genetic diversity of MRSA and methicillin-susceptible S. aureus (MSSA) recovered from hospital personnel in Tianjin, North China. Methodology. Three hundred and sixty-eight hand or nasal swabs were collected from 276 hospital personnel in 4 tertiary hospitals in Tianjin, North China between November 2017 and March 2019. In total, 535 Gram-positive bacteria were isolated, of which 59 were identified as S. aureus . Staphylococcal cassette chromosome mec (SCC mec ) typing, multi-locus sequence typing (MLST) and spa typing were performed to determine the molecular characteristics of S. aureus . Results. Thirty-one out of 276 (11 %) hospital personnel were S. aureus carriers, whereas 11/276 (4 %) carried MRSA. Fifty out of 59 (85 %) S. aureus isolates were resistant or intermediately resistant to erythromycin. The dominant genotypes of MRSA recovered from hospital personnel were ST398-t034-SCC mec IV/V and ST630-t084/t2196, whereas the major genotypes of MSSA included ST15-t078/t084/t346/t796/t8862/t8945/t11653 and ST398-t189/t034/t078/t084/t14014. Conclusion. Although the predominant genotypes of MRSA recovered from hospital personnel in this study were different from the main genotypes that have previously been reported to cause infections in Tianjin and in other geographical areas of China, the MRSA ST398-t034 genotype has previously been reported to be associated with livestock globally. The dominant MSSA genotypes recovered from hospital personnel were consistent with the those previously reported to have been recovered from the clinic.